RANCANG BANGUN ALARM ANTI PUTUS - Khalil, Muhammad; Musthofa, Imron; Artika, Kurnia Dwi; Andriami, Sri Muntiah; Wicaksono, Bayu Agung (POLITALA PRESS, 2024)
Technology can be used as a preventive measure to avoid theft. One technology that can interfere and even make the perpetrator cancel the robbery is an alarm. With the sound of the alarm, the thief can be surprised and will immediately save himself because he is worried about being caught. Until now, various alarm technologies have been studied, from simple to complex. There are also many sensors used as triggers for alarm activation. This study created a simple anti-break alarm that is not easily turned off using a magnetic switch and relay. Several parameters are measured to determine the performance of the input and output of the alarm such as voltage and current, then a consistency test is carried out from the alarm that was created. The results obtained were that the alarm functioned properly. The alarm can sound when the door is opened then continues to sound and does not break when the door is closed again. The alarm also works consistently after 100 tests.